Oculo-orbital non-Hodgkin´s lymphoma: a retrospective study of 9 patients - Ghorbel, Asma; Abidi, Rim; Yousfi, Amani; Ben Amor, Raouia; Yahyaoui, Safia; Zarraa, Samia; Mahjoubi, Khalil Ben; Belaid, Asma Ben; Nasr, Chiraz Ben (The Pan African medical journal, 2021)
Oculo-orbital non-Hodgkin lymphoma is a rare presentation of lymphoma. The objective of our study was to clarify the clinical features of non-Hodgkin´s oculo-orbital malignant lymphoma and to establish the place of radiotherapy in the treatment. This is a retrospective study including 9 patients treated at the Salah Azaiez Institute between 2007 and 2018. There were 5 women for 4 men with an average age of 65 years. Four LMNHs were located on the right, three on the left and two bilateral. The time between the appearance of functional signs and the diagnosis was less than 6 months. The diagnosis is confirmed by biopsy, resulting in several histological varieties. A full extension assessment was performed in all patients. Muscle and/or optic nerve extension was noted in 6 patients and bone damage was observed in two patients. Six patients had chemotherapy. The 9 patients were treated with orbital radiotherapy with a dose that varied between 30.6 and 40 Gy. The duration of patient follow-up was from 2 months to 10 years. Seven patients were in complete remission. Two patients had insufficient follow-up and one patient died one month after the end of treatment. The interest of radiotherapy in oculo-orbital LMNH has been clearly demonstrated in several studies, but its place, its methods and its tolerance profile remain to be defined in many situations.